2021
DOI: 10.30901/2658-6266-2020-4-o1
|View full text |Cite
|
Sign up to set email alerts
|

Nomenclatural standards and genetic passports of potato cultivars bred in the A.G. Lorkh All-Russian Research Institute of Potato Farming

Abstract: In order to preserve the genetic diversity of cultivars, it is recommended to develop documentation approaches through the registration of cultivar nomenclatural standards in accordance with the International Code of Nomenclature for Cultivated Plants. The N.I Vavilov Institute of Plant Genetic Resources keeps developing this approach along with the DNA marker technologies: SSR genotyping and molecular screening with DNA markers of genes controlling valuable traits. In 2018, VIR, together with the leading nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 51 publications
0
7
0
4
Order By: Relevance
“…According to A. Barone with colleagues (1990) [84], a major dominant gene Gro1 confers resistance to all pathotypes of G. rostochiensis including Ro5. In our previous research it was shown the extremely low frequency of the Gro1-4 marker in the Russian cultivar genepool [42,[56][57][58][59]. A few Gro1-4-positive cultivars were involved in the present study, however, any association with resistance to Ro5 pathotype was not detected.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…According to A. Barone with colleagues (1990) [84], a major dominant gene Gro1 confers resistance to all pathotypes of G. rostochiensis including Ro5. In our previous research it was shown the extremely low frequency of the Gro1-4 marker in the Russian cultivar genepool [42,[56][57][58][59]. A few Gro1-4-positive cultivars were involved in the present study, however, any association with resistance to Ro5 pathotype was not detected.…”
Section: Discussionmentioning
confidence: 48%
“…The obtained results indicated high (87%) predictive association between the presence of two markers of the H1 gene-57R and TG689-and phenotypic resistance to Ro1. The diagnostic value of these markers can be increased up to 90% in the case of counting moderately resistant cultivars as resistant genotypes [42,[56][57][58][59]. This study also demonstrated the extremely low frequency of Gro1-4 resistance-predictive allele within the subset of Russian potato cultivars.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations